PSYCHOPATHOLOGY IN THE AFTERMATH OF THE HAITI EARTHQUAKE: A POPULATION‐BASED STUDY OF POSTTRAUMATIC STRESS DISORDER AND MAJOR DEPRESSION. Issue 5 (1st November 2012) - Cerdá, Magdalena; Paczkowski, Magdalena; Galea, Sandro; Nemethy, Kevin; Péan, Claude; Desvarieux, Moïse
<x xml:space="preserve">Abstract</x> Background In the first population‐based study of psychopathology conducted in Haiti, we documented earthquake‐related experiences associated with risk for posttraumatic stress disorder (PTSD) and major depressive disorder (MDD) 2–4 months following the 2010 Haiti earthquake. Methods A population‐based survey was conducted of 1, 323 survivors randomly selected from the general nondisplaced community, internally displaced persons camps, and a community clinic. Respondents were from the Nazon area of Port‐au‐Prince, ∼20 miles from the epicenter. Results Respondents (90.5%) reported at least one relative/close friend injured/killed, 93% saw dead bodies, and 20.9% lost their job post‐earthquake. The prevalence of PTSD (24.6%) and MDD (28.3%) was high. History of violent trauma was associated with risk of PTSD and MDD (adjusted odds ratio [AOR] 1.4, 95% confidence interval [CI], 1.0–1.9; AOR, 1.7, 95% CI 1.3, 2.2, respectively). Low social support (AOR, 1.7, 95% CI 1.2, 2.3; AOR 1.4, 95% CI 1.0, 1.9, respectively) increased risk of PTSD and MDD among women. Suffering damage to the home increased risk of MDD in males (AOR 2.8, 95% CI 1.5, 5.5). Associations between being trapped in rubble, major damage to house, job loss, and PTSD; and participation in rescue/recovery, friends/family injured/killed, and MDD varied based on prior history of violent trauma. Conclusions Addressing mental health in a post‐earthquake setting such as Haiti will require focusing resources on screening and treatment of identified vulnerable groups while targeting improvement of post‐earthquake living conditions. Investment in sources of social support for women may make help mitigate the vulnerability of women to PTSD and MDD.